2016
DOI: 10.1007/s00276-016-1730-x
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic study of the anterior cruciate ligament of the knee using an open MRI

Abstract: Recent anatomical and radiological studies of the anterior cruciate ligament (ACL) suggest the ACL length and orientation change during knee flexion, and an open MRI sequencing during knee flexion enables a dynamic ACL analysis. This study's goal is to describe a normal ACL using a 1T open MRI and, in particular, variations in length and insertion angles at different degrees of flexion. Twenty-one volunteers with clinically healthy knees received a dynamic MRI with their knees in hyperextension, neutral positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The experimental setup was selected to isolate the effects of the tunnel drilling technique and has its limitations. This includes a static angle at which the load is applied, which does not fully replicate the changing bending angles of an ACL at the femoral and tibial apertures during flexion and extension 2534). While graft ruptures are more frequently found at the aperture of the femoral tunnel, any portion where the graft bends over a bony edge could be a source of graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup was selected to isolate the effects of the tunnel drilling technique and has its limitations. This includes a static angle at which the load is applied, which does not fully replicate the changing bending angles of an ACL at the femoral and tibial apertures during flexion and extension 2534). While graft ruptures are more frequently found at the aperture of the femoral tunnel, any portion where the graft bends over a bony edge could be a source of graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who had any suspicion of the ACL insufficiency at the physical examination in the hospital electronic medical records not included in the degeneration group. Another limitation is the knee joint position in the MRI examination, which can affect the angle measurements, as mentioned by Guenoun et al [29]. However, we routinely obtained all knee MRI examinations during full extension of the knee similar to most of the studies compared [3,7,10], but the position of the knee in the study by performed Mellado et al [11] was not exactly stated.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the sagittal angle of the ACL ranges from 45° to 20° with increasing knee joint flexion. 16 This factor affects the measurements in a clinical setting, as even the slightest flexion during CT or MRI will change the angle of the ACL graft. Furthermore, even if the angle is correct, the placement may still be faulty if the graft is placed too anteriorly or too posteriorly.…”
Section: Discussionmentioning
confidence: 99%